Answer: its 3 🙂 Step-by-step explanation: Simplifying 8 + -1(4x + 7) = 5(x + 6) + -2 Reorder the terms: 8 + -1(7 + 4x) = 5(x + 6) + -2 8 + (7 * -1 + 4x * -1) = 5(x + 6) + -2 8 + (-7 + -4x) = 5(x + 6) + -2 Combine like terms: 8 + -7 = 1 1 + -4x = 5(x + 6) + -2 Reorder the terms: 1 + -4x = 5(6 + x) + -2 1 + -4x = (6 * 5 + x * 5) + -2 1 + -4x = (30 + 5x) + -2 Reorder the terms: 1 + -4x = 30 + -2 + 5x Combine like terms: 30 + -2 = 28 1 + -4x = 28 + 5x Solving 1 + -4x = 28 + 5x Solving for variable ‘x’. Move all terms containing x to the left, all other terms to the right. Add ‘-5x’ to each side of the equation. 1 + -4x + -5x = 28 + 5x + -5x Combine like terms: -4x + -5x = -9x 1 + -9x = 28 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -9x = 28 + 0 1 + -9x = 28 Add ‘-1’ to each side of the equation. 1 + -1 + -9x = 28 + -1 Combine like terms: 1 + -1 = 0 0 + -9x = 28 + -1 -9x = 28 + -1 Combine like terms: 28 + -1 = 27 -9x = 27 Divide each side by ‘-9’. x = -3 Simplifying x = -3 Log in to Reply

Answer: [tex]x=\frac{-29}{9} \\x=-3.2\\x=-3\frac{2}{9}[/tex] 1st answer: Exact Form 2nd answer: Decimal Form 3rd answer: Mixed Number Form Log in to Reply

Answer:its 3 🙂

Step-by-step explanation:Simplifying

8 + -1(4x + 7) = 5(x + 6) + -2

Reorder the terms:

8 + -1(7 + 4x) = 5(x + 6) + -2

8 + (7 * -1 + 4x * -1) = 5(x + 6) + -2

8 + (-7 + -4x) = 5(x + 6) + -2

Combine like terms: 8 + -7 = 1

1 + -4x = 5(x + 6) + -2

Reorder the terms:

1 + -4x = 5(6 + x) + -2

1 + -4x = (6 * 5 + x * 5) + -2

1 + -4x = (30 + 5x) + -2

Reorder the terms:

1 + -4x = 30 + -2 + 5x

Combine like terms: 30 + -2 = 28

1 + -4x = 28 + 5x

Solving

1 + -4x = 28 + 5x

Solving for variable ‘x’.

Move all terms containing x to the left, all other terms to the right.

Add ‘-5x’ to each side of the equation.

1 + -4x + -5x = 28 + 5x + -5x

Combine like terms: -4x + -5x = -9x

1 + -9x = 28 + 5x + -5x

Combine like terms: 5x + -5x = 0

1 + -9x = 28 + 0

1 + -9x = 28

Add ‘-1’ to each side of the equation.

1 + -1 + -9x = 28 + -1

Combine like terms: 1 + -1 = 0

0 + -9x = 28 + -1

-9x = 28 + -1

Combine like terms: 28 + -1 = 27

-9x = 27

Divide each side by ‘-9’.

x = -3

Simplifying

x = -3

Answer:[tex]x=\frac{-29}{9} \\x=-3.2\\x=-3\frac{2}{9}[/tex]

1st answer: Exact Form

2nd answer: Decimal Form

3rd answer: Mixed Number Form